2012
DOI: 10.1128/jb.02171-12
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Protein Interaction Domains of Bacillus subtilis DivIVA

Abstract: e DivIVA proteins are curvature-sensitive membrane binding proteins that recruit other proteins to the poles and the division septum. They consist of a conserved N-terminal lipid binding domain fused to a less conserved C-terminal domain. DivIVA homologues interact with different proteins involved in cell division, chromosome segregation, genetic competence, or cell wall synthesis. It is unknown how DivIVA interacts with these proteins, and we used the interaction of Bacillus subtilis DivIVA with MinJ and RacA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 36 publications
3
57
0
Order By: Relevance
“…subtilis DivIVA is not functional in L. monocytogenes. Previous work has shown that DivIVA from L. monocytogenes (DivIVA Lm ) is not functional in B. subtilis, even though the two proteins share 65% sequence identity (18) and are almost of the same length (175 versus 164 amino acids, respectively) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…subtilis DivIVA is not functional in L. monocytogenes. Previous work has shown that DivIVA from L. monocytogenes (DivIVA Lm ) is not functional in B. subtilis, even though the two proteins share 65% sequence identity (18) and are almost of the same length (175 versus 164 amino acids, respectively) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 97%
“…Hydrophobic amino acids are exposed to the solvent at the apical end of this structure, and DivIVA interacts with membranes through the insertion of these side chains into the phospholipid bilayer (16,17). In addition to membrane binding, the lipid binding domain also mediates the interaction of DivIVA with binding partners, such as MinJ (18). In Bacillus subtilis, MinJ serves as a molecular bridge between DivIVA and MinD to ensure septal and polar recruitment of the division site selection proteins MinCD (10,11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The HGT organism in this data set is Bacillus subtilis BSN238, a transgenic organism that is a chimera of B. subtilis 168 where the DivIVA protein has been replaced with the DivIVA from Listeria monocytogenes strain EGD-e (van Baarle et al, 2012). The Listeria DivIVA protein is located on the complement strand at positions 2'100'224-2'100'751 (NC 003210.1).…”
Section: Experimental Setup Data Setsmentioning
confidence: 99%